The World's Most Beautiful Blue - Rudolph, Cedric (Christianity & literature, 2018)
The poem "The World's Most Beautiful Blue," by Cedric Rudolph is presented. First Line: and it's slapped on some highway overpass. Last Line: "Yes, I'll use this later."